STATE OF DEVELOPMENT AND APPLICATION OF ECO-ORIENTED PEDAGOGICAL TECHNOLOGIES IN PROFESSIONAL TRAINING OF FUTURE QUALIFIED WORKERS (Innovative professional education, 2023)
The study of the state of development and application of eco-oriented pedagogical technologies in the professional training of future skilled workers makes it possible to conclude that the quality of professional training of future skilled workers in the construction, agricultural and restaurant industries will increase if: theoretically justify and implement a methodical system that integrates methods from the use of eco-oriented pedagogical technologies and to develop the readiness of pedagogical workers for their development and application in the professional training of future qualified workers.
Keywords: pedagogical technologies, eco-oriented learning technologies, methodical system of development and application of eco-oriented pedagogical technologies